2014
DOI: 10.5603/cj.a2013.0148
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio predicts short- and long-term mortality following revascularization therapy for ST elevation myocardial infarction

Abstract: (OR = 5.35, p < 0.001), cerebrovascular accident history (OR = 3.36, p = 0.023), low glomerular filtration rate (OR = 0.98, p = 0.012) and cardiac arrest on admission (OR = 17.43, p < 0.001) as robust independent predictors of long-term mortality. NLR was divided into two sub-groups based on an optimal cut off value of 7.4. This provided the best discriminatory cut off point for predicting adverse mortality outcome. (Cardiol J 2014; 21, 5: 500-508)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
69
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 30 publications
11
69
2
4
Order By: Relevance
“…(14) NLR has been studied by different investigators in relation to different scoring systems showing CAD severity and it has been shown to be related to NLR by SYNTAX, GRACE and TIMI scores. (15)(16)(17) In our study, similarly, the NLR values were higher in the ACS group than in the control group. Correlation analyzes showed that NLR correlated with high sensitive troponin I, PLR, ST elevation, ST depression, T wave negativity and angina duration.…”
Section: Discussionsupporting
confidence: 58%
“…(14) NLR has been studied by different investigators in relation to different scoring systems showing CAD severity and it has been shown to be related to NLR by SYNTAX, GRACE and TIMI scores. (15)(16)(17) In our study, similarly, the NLR values were higher in the ACS group than in the control group. Correlation analyzes showed that NLR correlated with high sensitive troponin I, PLR, ST elevation, ST depression, T wave negativity and angina duration.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, growing interest has been directed towards leukocyte subtypes and especially the neutrophil-to-lymphocyte ratio (NLR), an inexpensive and convenient way to identify inflammatory parameters, and potentially an even more accurate indicator of cardiovascular risk than absolute blood cell counts [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…17 More recently, attention has shifted to leukocyte subtypes and to the neutrophil to lymphocyte ratio (NLR), potentially being more accurate and stable than absolute blood cell counts, especially in patients with acute presentation, where it has been associated with clinical outcome and procedural results after percutaneous revascularization. 18,19 However, few reports have evaluated the relationship between NLR and the prevalence and extent of CAD; this was the aim of the present study.…”
Section: Introductionmentioning
confidence: 99%